Implementasi Model PBL untuk Pembelajaran Matematika pada Sekolah Dasar - Alisia Zahro’Atul Baroroh; Umi Mahmudah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Mathematics learning in elementary schools still faces several challenges, including low student motivation and critical thinking skills. One innovative solution is the implementation of the Problem Based Learning (PBL) model. This study aims to examine the effectiveness of PBL in improving elementary students’ conceptual understanding and critical thinking in mathematics. This research employed a Classroom Action Research (CAR) method conducted in two cycles involving fifth-grade students at [School Name] Elementary School. Data were collected through observations, tests, interviews, and documentation. The results show that the implementation of the PBL model increased student engagement, problem-solving ability, and the average score of conceptual understanding in mathematics. Therefore, PBL is proven to be effective in fostering meaningful learning and promoting higher-order thinking skills. It is recommended that elementary mathematics teachers integrate PBL as a student-centered learning approach.